Early Motor Milestones in Infancy and Later Motor Impairments: A Population-Based Data Linkage Study - Hua, Jing; Williams, Gareth J.; Jin, Hua; Chen, Juan; Xu, Manyun; Zhou, Yingchun; Gu, Guixiong; Du, Wenchong (Frontiers in Psychiatry, 2022)
Background: Developmental Coordination Disorder (DCD) is a neurodevelopmental condition with high prevalence. Early motor milestones are important markers to identify DCD. The current study aims to evaluate the association between the onset of crawling and independent walking and their transition pattern during infancy and later motor impairments. Methods: A total of 8395 children aged 3-6 years old in China were included in the final analysis. A parent questionnaire was used to collect early milestone onset data. Children’s motor performance was measured using the Movement Assessment Battery for Children-2nd edition (MABC-2). The association between motor milestones and motor impairment was analyzed using a multilevel regression model. Results: The result showed that a one-month delay in crawling onset increased the risk of significant overall motor impairment by 5.3%, and 14.0% when adjusting for child and family characteristics. A one-month delay in walking onset increased the risk of significant overall motor, fine, gross, and balance impairment by 21.7%, 8.3%, 13.3%, and 17.8%. A one month increase in the transition time from crawling to independent walking increased the risk of significant overall motor and gross motor impairment by 7.7% and 6.6%. These results were inconsistent across different age bands (each p<0.05). Conclusions: Our study indicates that even a mild delay in crawling and walking onsets in infancy increase the risk for subsequent motor impairments in childhood, and children with motor impairments revealed a different transition pattern from crawling to walking. The motor abilities of children with motor impairments can be observed to diverge from typically developing children as early as 6-8 months old. The findings can facilitate the early identification of motor impairments in children, and provide early signs to initiate intervention.